VUV irradiance measurement of a 2.45 GHz microwave-driven hydrogen discharge. (13th August 2015) - Komppula, J; Tarvainen, O; Kalvas, T; Koivisto, H; Kronholm, R; Laulainen, J; Myllyperkiö, P
Abstract: Absolute values of VUV-emission of a 2.45 GHz microwave-driven hydrogen discharge are reported. The measurements were performed with a robust and straightforward method based on a photodiode and optical filters. It was found that the volumetric photon emission rate in the VUV-range (80–250 nm) is 10 16 –10 17  cm −3 s −1, which corresponds to approximately 8% dissipation of injected microwave power by VUV photon emission. The volumetric emission of characteristic emission bands was utilized to diagnostics of molecular plasma processes including volumetric rates of ionization, dissociation and excitation to high vibrational levels and metastable states. The estimated reaction rates imply that each injected molecule experiences several inelastic electron impact collisions. The upper limit for the total density of metastable neutrals (2S atoms and molecules) was estimated to be approximately 0.5% of the neutral gas density.